Autism, discrimination and the law : a quick guide for parents, educators and employers - Graham, James (Jessica Kingsley Publishers, 2008)
"Autism, Discrimination and the Law" outlines how the legal requirements of the Disability Discrimination Act 1995 might be met for students and employees with autism spectrum disorders (ASDs). What might discrimination against people with autism look like? What can you do to prevent discrimination against people with autism? What should you do if you have been discriminated against?The book includes an overview of current knowledge of autism, and details of the changes in legislation concerning disability discrimination. The main part of the book is devoted to case studies from further education and employment demonstrating how reasonable adjustments can be made successfully. This accessible book will be an essential reference for employers, policy makers, local education authorities, learning and skills councils, training providers, schools and colleges, personnel officers, careers officers, charities, residential homes, parents, and indeed anyone working with people with autistic spectrum disorders.